Electrophysiology Echoes Brain Dynamics in Children and Adolescents With Tourette Syndrome—A Developmental Perspective - Rothenberger, Aribert; Heinrich, Hartmut (Frontiers in Neurology, 2021)
The development of the complex clinical picture of motor and vocal tics in children and adolescents with Tourette syndrome (TS) must be paralleled by changes in the underlying pathophysiology. Electrophysiological methods such as EEG and event-related potentials (ERPs) are non-invasive, safe and easy to apply and thus seem to provide an adequate means to investigate brain dynamics during this brain maturational period. Also, electrophysiology is characterized by a high time resolution and can reflect motor, sensory and cognitive aspects as well as sleep behavior. Hence, this narrative review focuses on how electrophysiology echoes brain dynamics during development of youngsters with TS and might be useful for the treatment of tics. A comprehensive picture of developmental brain dynamics could be revealed showing that electrophysiological parameters evolve concurrently with clinical characteristics of TS. Specifically, evidence for a maturational delay of motor inhibition related to cortico-spinal hyper-excitability and brain mechanisms for its cognitive compensation could be shown. Moreover, deviant sleep parameters and probably a stronger perception-action binding were reported. For neuromodulatory treatments (e.g., neurofeedback; repetitive transcranial magnetic stimulation, rTMS / transcranial direct current stimulation, tDCS) targeting neuronal deficits and/or strengthening compensatory brain mechanisms, pilot studies support the possibility of positive effects regarding tic reduction. Finally, attention-deficit / hyperactivity disorder (ADHD), as a highly frequent co-existing disorder with TS, has to be considered when using and interpreting electrophysiological measures in TS. In conclusion, application of electrophysiology seems to be promising regarding clinical and research aspects in youngsters with TS.